2016
DOI: 10.1016/j.ijpsycho.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Performance monitoring in autism spectrum disorders: A systematic literature review of event-related potential studies

Abstract: Autism spectrum disorder (ASD) is marked by impairments in social-emotional situations, executive functioning, and behavioral regulation. These symptoms may be related to deficits in performance monitoring, i.e., the ability to observe and evaluate one's own behavior and performance which is necessary for the regulation of future behavior. The present literature review investigated electroencephalic correlates of performance monitoring in ASD. Event-related potentials (ERPs) considered in this review included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 89 publications
(208 reference statements)
5
16
1
Order By: Relevance
“…It is possible, however, that the pattern across the three ERP components examined in this review has greater specificity. A recent review reported a similar pattern of decreased early performance monitoring (ERN) accompanied by relatively intact Pe and FN in people with autism spectrum disorders (Hupen et al, 2016). These comparable patterns are intriguing to consider in the context of the longstanding interest in the potential overlapping vulnerability to psychosis and autism spectrum disorders (Stone and Iguchi, 2011).…”
Section: Discussionmentioning
confidence: 87%
“…It is possible, however, that the pattern across the three ERP components examined in this review has greater specificity. A recent review reported a similar pattern of decreased early performance monitoring (ERN) accompanied by relatively intact Pe and FN in people with autism spectrum disorders (Hupen et al, 2016). These comparable patterns are intriguing to consider in the context of the longstanding interest in the potential overlapping vulnerability to psychosis and autism spectrum disorders (Stone and Iguchi, 2011).…”
Section: Discussionmentioning
confidence: 87%
“…Though it is not the only ability that is critical for smooth navigation of the social world, the ability of error‐monitoring has been argued to relate to the social impairments seen in individuals with ASD [Hüpen et al, , Mundy, ], as an awareness of errors can apply to multiple domains involved in real‐life interactions. Perceptual decision‐making and interval timing seem to be two cognitive domains with particular significance for the social difficulties in ASD, where inferring meaning from visual input and arranging the timing of verbal and nonverbal responses in communications are crucial for conducting smooth social interactions [e.g., Barraclough et al, ; Lambrechts et al, ; Sokhadze et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…These ERP components differed in individuals with ASD from those of TD controls, which suggest lower sensitivity in the detection and monitoring of errors in ASD. Additionally, a review of available performance monitoring findings in ASD concludes reduced performance monitoring in ASD as measured by ERN and error positivity [Hüpen et al, ]. These neurophysiological findings suggest disrupted error‐monitoring in individuals with ASD, which is yet to be confirmed across different cognitive domains.…”
Section: Introductionmentioning
confidence: 99%
“…However, support for this idea using ERPs has been mixed, perhaps due to reward paradigms that differ with respect to probabilistic and learning features as well as whether feedback is concrete or abstract (see Hüpen, Groen, Gaastra, Tucha, & Tucha, 2016). Two studies by Crowley and colleagues (Larson, South, Krauskopf, Clawson, & Crowley, 2011; McPartland et al, 2012), one dataset which is included in the current study, did not find reliable differences in FRN amplitude between age and IQ-matched cohorts of ASD and neurotypical controls.…”
Section: Introductionmentioning
confidence: 99%